Rwanda Employment and Jobs Study - World Bank (Washington, DC, 2015)
Fast growth in Rwanda since the turn of the century has been accompanied by solid poverty reduction. Between 2000 and 2013, gross domestic product (GDP) grew at eight percent per year, resulting in a 170 percent increase in real GDP. As the poor almost uniquely depend on labor to generate income, the strong reduction in poverty suggests tangible improvements in employment outcomes over this period. This jobs and employment study focuses on the recent dynamics in Rwanda’s jobs’ landscape. Using data from a variety of sources, mainly the three integrated households living conditions surveys (EICV1, EICV2, and EICV3) and the 2011 establishment census, the report looks at what workers in Rwanda are doing and what they are making, and how this has changed over the past ten to fifteen years. Most of the report focuses on the five years between 2006 and 2011, although at times, the authors will also look at the evolution since 2001. The report concludes with a number of ideas to address Rwanda’s jobs challenge in the near future.